ANALISIS ENTREPRENEURIAL LEADERSHIP DAN HAMBATAN PERTUMBUHAN USAHA DI UMKM PENGOLAHAN TAHU "RDS" SINGOSARI MALANG - Aris Wahyu Tristanto; Ludi Wishnu Wardana (Universitas Negeri Surabaya, 2018)
This research was conducted to describe the entrepreneurial leadership of SMEs Tofu "RDS" and description about the obstacles experienced by SMEs Tofu "RDS". This research uses descriptive qualitative research design that aims to obtain the information available at this time, and then attempt to describe, record and interpret the information. Data collection methods used were interviews, observation and documentation. This type of qualitative research is case study. The result of the research is the condition of entrepreneurial leadership from the leadership of SMEs Tofu "RDS" is generally good because he is able to motivate employees well, have a picture of the future effort, able to read opportunities well, actively seeking new ideas, persistent in running their business And barriers faced by SMEs Tofu "RDS" can be overcome well by the leadership of SMEs Tofu RDS.